Electrical properties studies of solid polymer electrolytes membrane based on carboxymethyl cellulose (CMC)/kappa carrageenan blend - Nur Khalidah, Zainuddin; Ahmad Salihin, Samsudin (American Institute of Physics Inc., 2018)
Polymer electrolyte membrane (PEMs) based on carboxymethyl cellulose (CMC) and kappa carrageenan (KC) was successfully prepared by using solution casting technique. The electrical conductivity and thermal conductivity of PEMs system have been measured by the Electrical impedance spectroscopy method in the temperature range of 303K. The PEMs system containing 80: 20 ratio of KC exhibits the highest conductivity of 3.19 x 10−7 S/cm at room temperature. It can be concluded that with CMC/KC blend is accountable for the conductance and assist in the ionic conductivity of the PEMs system. The dielectric behavior study reveals the non-Debye properties of the PEMs system.